Peningkatan Pemahaman IoT dan VR melalui Game Edukatif Interaktif di PKBM Banyutowo - Arden, Septian Cesare; Krismawan, Yosef Argo; Husnianto, Naufal; Raisal, Muhammad Hafidz; Ali, Zidan Firkhan; Santi, Mustika Bintang Pramudya; Thamariska, Rhema; Saputra, Muhammad Faried; Atmoko, Khoirul Huda Indra; Budiyanto, Cucuk Wawan (FKIP Universitas Sebelas Maret, 2025)
The high interest in technology at PKBM Banyutowo, which is not matched by the availability of devices, encourages the implementation of this community service activity. This community service initiative aims to enhance students' understanding and skills in Internet of Things (IoT) and Virtual Reality (VR) technologies through interactive learning methods using educational games. The program was conducted at PKBM Banyutowo , involving 10 elementary school participants. The implementation comprised three stages: preparation (developing IoT devices and VR games), execution (hands-on practice and simulations), and evaluation (via quizzes and reflections). Results indicated significant improvements in participants' grasp of IoT concepts and their enthusiasm for VR simulations. Challenges such as programming complexity and device availability were addressed through intensive mentoring and structured learning modules. The activity not only strengthened participants' technical competencies but also fostered sustained interest in digital technologies.